Visionary Leadership in the Transformation of Islamic Education in the Era of Disruption - Liliana, Liliana; Almuhajir, Almuhajir (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
Visionary leadership is defined as a leadership style that always puts forward a vision and makes decisions to realize it. So that what is expected in visionary leadership is able to stand up to the transformation of Islamic education in today's modern era. This study aims to analyze the role of visionary leadership in the transformation of Islamic education in the era of disruption. The method used is Library research with a qualitative descriptive approach, reviewing various literature related to visionary leadership, Islamic education, and educational competitiveness. The results showed that visionary leadership in Islamic education in the Disruption era emphasizes the formulation of a long-term vision that has a high level of inspiration and motivation. Visionary leaders lead by prioritizing innovation, adaptation, and human resource development to realize better education. Visionary leadership prioritizes investment in infrastructure and technology for quality education, as well as formulating policies that support the improvement of the quality of education, both academically and non-academically, with an emphasis on developing digitalization innovations, moral aspects and the character of students, so that continuous evaluation and improvement are also important things from visionary leadership.